Recent Advances in Genetically Engineered Microorganisms and their Risks: A Review - Gari, Jiregna; Teshome, Ibsa; Shasho, Bekiyad (International Journal on Food, Agriculture and Natural Resources, 2023)
Genetically engineered microorganisms have applications in various domains, such as agriculture, bioscience, healthcare, life sciences, and research. The novel methods of the system Clustered Regularly Interspaced Short Palindromic Repeats associated with protein 9, which originates from archaeal and bacterial immune systems and allows significant improvements to modified strains of microorganisms, represented a major innovation in industrial biotechnology. The rapid advancement of genetically engineered microorganisms has shown potential for bioremediation, food enzyme production, probiotics, and pesticides. Recently, engineered microbes have been used in several industries, like dairy, pharmaceuticals, biotech, and agrochemicals. Modified microorganisms used as biosensors are improved with reporter genes that induce their expression depending on the nature and concentration of the compound of interest to monitor environmental pollution. Genetically engineered microorganisms have been considered a threat to the environment, animals, and human health. Insertion of a single gene into different cells can result in diverse outcomes, and the general pattern of gene expression can be changed. More advanced and better techniques should be developed and applied in the genetic engineering of microbes to minimize risks.